DIALOGIC RELATIONSHIP WITH PATIENTS REGARDING KIDNEY TRANSPLANTATION: NURSING EDUCATIONAL CARE - Simone Aparecida Machado do Nascimento Ferreira; Maria Luiza de Oliveira Teixeira; Elen Martins da Silva Castelo Branco (Universidade Federal do Paraná, 2018)
Objective: to describe the knowledge of chronic kidney patients about kidney transplantation, and discuss the contributions of this knowledge to nursing educational care. Method: this is a convergent-care study with 11 chronic kidney disease patients who were eligible for transplantation, at a university hospital in the city of Rio de Janeiro. Individual interviews were conducted between March 2016 and February 2017, and their content submitted to thematic content analysis. Results: the results bring the reflection that chronically ill people need integrated actions with the participation of several areas of health knowledge. It is imperative that patients share the experience of those who live with chronic illnesses with health professionals through a critical-reflexive dialogue. Conclusion: the dialogue allowed the reflection on the construction and reconstruction of knowledge and practices about kidney transplantation, and revealed co-responsibility among professionals, patients and their families in the process of recovery from the surgical procedure, and graft maintenance.